An exploration of the mechanisms of action of transcranial direct current stimulation (tDCS) in mood and anxiety disorder research - Ironside, M; Harmer, C; O'Shea, J; Ebmeier, K; Brunoni, A (2016)
The difficulty in treating mood and anxiety disorders has brought about renewed clinical interest in alternative treatments, such as transcranial direct current stimulation (tDCS) of the dorsolateral prefrontal cortex (DLPFC). However, the optimal parameters for stimulation and underlying mechanisms of action are unclear. Psychiatric treatments have acute effects on emotional processing which predict later therapeutic action. Such effects have been proposed as cognitive biomarkers for screening novel treatments for depression and anxiety disorders. In this thesis the proposed cognitive, behavioural and neural underpinnings of mood and anxiety disorders are explored using tDCS of the DLPFC in humans. This is investigated with a series of studies which measure the acute effects of tDCS on emotional processing relevant to depression and trait anxiety or anxiety disorders. An initial investigation in healthy volunteers revealed an anxiolytic like effect (reduced threat vigilance) of a single session of tDCS on a behavioural test of proven clinical relevance. In addition, stimulation parameters were refined for future studies. The subsequent two behavioural investigations combined tDCS with an attentional bias modification (ABM) training paradigm. However, no bias modification was achieved in these studies and predictably, no subsequent effects on attentional bias, mood/ trait anxiety or worry were observed. The first of the ABM investigations included a measure of cortisol awakening response (CAR) and it was found that a single session of tDCS (regardless of ABM condition) reduced subsequent CAR in healthy volunteers, also suggesting an anxiolytic effect. The final study, in a sample of trait anxious females, used functional imaging to reveal that tDCS of the DLPFC increased frontal activation and reduced amygdala response to fearful face distractors during low cognitive effort. This provides the first causal evidence that modulating activity directly in the DLPFC inhibits amygdala response to threat in humans, and provides a potential neural mechanism for the previous reduction in vigilance to threat, and also for the efficacy of tDCS in the treatment of depression and anxiety disorders. The evidence from this thesis puts forward an anxiolytic-like effect of frontal tDCS on cognitive, neural and adrenal biomarkers relevant to clinical anxiety disorders, and indicates a potential cognitive mechanism (reduced fear vigilance) and an underlying neural mechanism (increased top-down control of amygdala response) that may partially mediate the reported clinical efficacy of prefrontal tDCS in the literature.